SISTEM PENDETEKSI KEASLIAN NOMINAL UANG KERTAS UNTUK TUNANETRA DENGAN SENSOR WARNA DAN SISTEM SUARA - Zuhair, Alvin; Trisna Pambudi, Kukuh; Syukron, Muhammad; Prasetyaningtyas, Antika; Baggas Pratama, Tegar (Politeknik Negeri Indramayu, 2025)
This banknote denomination and authenticity detection system was designed using an Arduino Uno Atmega 328P microcontroller as the main controller. Two sensors were employed: Sensor A (RGB) to read the color patterns of banknotes for denomination classification, and Sensor B combined with an ultraviolet lamp to verify the presence of security features. The data processing flow is sequential: the denomination is first recognized through RGB analysis, followed by authenticity verification under UV detection. The results are delivered through an audio output, announcing the denomination if the banknote is genuine, or issuing a warning “banknote not detected” if it is counterfeit. The evaluation of the system focused on two main parameters: security and efficiency. Security was measured by the accuracy in distinguishing genuine from counterfeit banknotes, the error rate (false positives and false negatives), and the reliability of the audio output in conveying the correct information. Efficiency was assessed in terms of system response time from banknote input to audio output, the success rate of correct denomination recognition, and the ease of use for visually impaired users.